Steatocystoma Multiplex pada Vulva Dengan Prosedur Elektrokauterisasi: Laporan Kasus - A A Ayu Adisti Nina Yuniandari; Firda Fakhrena; Diana Wijayanti (Jurnal Health Sains, 2022)
Steatocystoma multiplex is a type of skin disorder in the form of asymptomatic intradermal cysts content of sebum. We report a 36-year-old female patient who came to the hospital with complaints of white, boil-like rashes on the vaginal lips and back appeared 1 year ago. The patient reported a history of the same complaint experienced by the patient's father, namely the appearance of white spots resembling boils in the back area. The results of the dermatological status examination showed that the lesions were regionally distributed ad regio labia majora and posterior thoracic inthe form of multiple discrete lesions, round in shape, measuring 0.1 cm x 0.1 cm x 0.5 cm to 0.2 cm x 0.2 mm. x 0.5 cm, well-defined, raised and dry lesions, and white papules. Based on history and physical examination, the patient was diagnosed with steatocystoma multiplex. We reported a rare case of steatocystoma multiplex at the vulva. Previous case management reports are one of the considerations for cauterization. The patient was given post-cautery therapy in the form of antibiotics levofloxacin 1 x 500 mg for 5 days and mefenamic acid 3 x 500 mg as painkillers